Financial Inclusion, Islamic Financial Literacy and Interest of Lamongan MSMEs to Use Islamic Bank Products - Abadi, Muhammad Dzikri; Purwanti, Ika; Hayat, Ardiansyah Ahsanul; Safitri, Putri Elfira; Safitri, Kavita Ayu (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2022)
Islamic banks have a strategic role in increasing the MSME business, especially in funding and supporting technical and non-technical assistance activities. Micro, Small and Medium Enterprises (MSMEs) are an inseparable part of business actors and play a significant role in creating job opportunities in Indonesia. Islamic banks to MSMEs in Lamongan. The purpose of this study was to determine the effect of financial inclusion on the interest of Lamongan SMEs with Islamic financial literacy as a moderating variable. The approach used in this research is a quantitative approach. The population used is MSMEs in Lamongan district with a sample of 138 respondents. The data obtained were then analyzed using SEM-PLS. The results of this study indicate that financial inclusion has a positive effect on interest in using Islamic bank products. Islamic financial literacy moderates the relationship between the influence of financial inclusion on interest in using Islamic banking services.